Oracle and PL/SQL recipes : a problem-solution approach - Juneau, Josh (Expert's voice in Oracle., 2010)
Oracle PL/SQL Recipes is your go to book for PL/SQL programming solutions. It takes a task-oriented approach to PL/SQL programming that lets you quickly look up a specific task and see the pattern for a solution. Then it's as simple as modifying the pattern for your specific application and implementing it. And you're done and home for dinner. Oracle PL/SQL Recipes is another in Apress' ongoing series of recipe books aimed at Oracle practitioners. The recipe format is ideal for the busy professional who just needs to get the job done. Covers the most common PL/SQL programming problems Presents solutions in ready-to-use format Stays short and to-the-point.